A Retrospective Study of 39 Patients Treated With Anterior Approach of Thoracic and Lumbar Spondylodiscitis: Clinical Manifestations, Anterior Surgical Treatment, and Outcome. Issue 47 (November 2015) - Yaldız, Can; Özdemir, Nail; Yaman, Onur; Feran, Hamit Günes; Tansug, Tugrul; Minoglu, Mustafa
Abstract : Abstract: The aim of this study is to report our 39 patients treated with anterior debridement and autologous iliac bone grafting with or without anterior instrumentation, which is the presumed treatment of choice for thoracic or lumbar spondylodiscitis. Our patients underwent surgical treatment of spondylodiscitis using anterior debridement and autologous iliac bone grafting with or without anterior instrumentation and were analyzed with a mean follow-up of 8 years (range, 2–11 years). Kaneda 2-rod system instrumentation was used in 12 patients, in total. Clinical outcomes were assessed by the Frankel grade. Radiographic fusion was characterized based on 3-dimensional computed tomography. Of the whole group, 20 patients suffered from tuberculous spondylodiscitis and 19 suffered from hematogenous spondylodiscitis. Pathogens responsible for pyogenic infection included Staphylococcus aureus (4 patients), Pseudomonas aeruginosa (3 patients), and Brucella melitensis (1 patient). Fifteen patients had thoracic involvement, 20 had lumbar involvement, and 4 had thoracolumbar junction involvement. Preoperative neurological deficits were noted in 13 of the 39 patients. In terms of Frankel grade, 8 patients have improved, 4 have remained the same, and 1 patient has worsened during the follow-up period. Imaging-documented fusion was achieved in 23 of 27 patients in the graft group (85% fusion rate) and 11 of 12 patients in the graft + Kaneda instrumentation group (91% fusion rate). There was no instrumentation failure, loosening, or graft-related complication such as slippage or fracture of the graft. This approach demonstrated a good recovery rate of neurological functions and a high fusion rate.